The Society Action Research Approach in the Development of Social Literacy in Schools and Communities - Syafa Layyina Amalia; Rida Ayu Agustina; Husni Umar Fadhilah; Muhammad Zuhrul Anam (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the implementation of Community Action Research (CAR) as a collaborative approach that integrates research, education, and social interaction to improve social literacy in schools and communities. SAR encourages active collaboration between teachers, students, and the community at every stage of the research process, from problem identification to reflection and capacity building. Factors supporting the success of SAR include active participation, school leadership, and daily availability, while its shortcomings stem from a lack of conceptual understanding, lack of facilities, and lack of motivation. The implementation of SAR strengthens the relationship between the educational community and the general public, improving social, emotional, and contextual literacy relevant to everyday life. In line with the 21st-century education paradigm that is student-centered and community-based, SAR creates a collaborative, reflective, and iterative learning process that encourages character development and community independence.